Cytomegalovirus Infection Modulates Cellular Immunity in an Experimental Model for Autoimmune Diabetes - Nienke van der Werf; Jan-Luuk Hillebrands; Flip A. Klatter; Ineke Bos; Cathrien A. Bruggeman; Jan Rozing (Clinical and Developmental Immunology)
Background: Viral infections are thought to play a role in the development of autoimmune diseases like type 1 diabetes. In this study we investigated the effect of Rat Cytomegalovirus (RCMV) infection on cellular immunity in a well-defined animal model for diabetes, the Biobreeding (BB) rat.